Development of a Coated-Micro-Particle Neutron Detector Based on LiF/ZnS Scintillator - Logoglu Faruk; Flaska Marek; Wolfe Douglas E. (EPJ Web of Conferences, 2020)
6LiF:ZnS(Ag) micro-particle neutron detectors are a promising technology to further improve neutron detection capabilities for a variety of applications. Specifically, we have been investigating 6LiF micro-particles coated with ZnS(Ag) to increase the neutron detection efficiency, light production, and light collection efficiency when compared to the existing powder-based technology (EJ-426 from Eljen Technology). Extensive radiation and light transport simulations with single micro-particles have been performed to find the optimal 6LiF diameter and ZnS(Ag) coating thickness. Full-scale multi-particle simulations also have been performed to determine the optimal pitch (particle-to-particle distance) and detector thickness. Randomizations of 6LiF radius, ZnS(Ag) coating thickness, position of particles, as well as shape of particles and partial coating have been performed to account for possible manufacturing imperfections. EJ-426 sheets have been modeled for reference purposes by defining spherical grains of 6LiF and ZnS(Ag) and compared against experiments. The simulation results show that the coated micro-particles should dramatically increase the neutron detection efficiency, light production, and light collection efficiency when compared to the existing EJ-426 technology.